Analisis Profitabilitas Pada Perbankan Konvensional Yang Menjalin Kerjasama Dengan Start Up Fintech - Dypsa Nehanka; Langgeng Prayitno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Disruptive technological developments in the era of the industrial revolution 4.0 make Financial Technology (Fintech) increasingly in demand. So that Fintech-based companies called Start Ups are growing rapidly. The ease of Fintech can be a threat to the Banking industry so that Conventional Banking is required to adapt. Therefore, in 2018 Bank BCA established a partnership with a Start Up called KlikAcc and Bank BRI with Go-Pay. This study aims to determine the effect of this collaboration on bank profitability in terms of bank profitability ratios, namely ROA, ROE, and NIM. This research is descriptive statistical with a quantitative approach, Data Source is secondary data obtained from the bank's official website. The technique of determining population is to take data from annual published financial statements. The sample size is the income statement for each annual period. Sampling technique with purposive sampling. Data collection procedures with documentation, literature studies and internet research. Data analysis techniques are profitability ratio analysis techniques and statistical analysis. Test Hypothesis using Difference Test (Sample T-Test). The results showed that at Bank BCA the variables ROA, ROE, and NIM did not have a significant effect. Meanwhile, Bank BRI has similar results where the variables ROA and ROE do not have a significant effect. While the NIM variable has a significant effect. Keywords: Financial Technology, Conventional Bank, Profitability Ratio